Gender wage differentials and its determinants for tenured academics at Universidad de Costa Rica - Blanco, Laura Cristina (2023)
Gender wage differentials for the tenured academic personnel at Universidad de Costa Rica are estimated using administrative datasets. Men’s average gross hourly wage is 7.8% higher than that of women, which is lower than the gender wage differential observed in the Costa Rican labor market for graduates. The gender wage differential for academics is completely explained, mainly by differences associated with human capital accumulation and research. Women have a lower probability than men of having a Ph.D. and of having studied at a top university. Since ascending the academic ladder is dependent on research, these characteristics are associated with women reporting less publications at the same time that their work is less valued by the institution.